Literary Hymns and Odes in the Grand Duchy of Lithuania in the 16ᵀᴴ–17ᵀᴴ Centuries: Origins - Staišiūnaitė, Viktorija (Literatūra, 2016)
Hymns and odes are known today as a praising and laudatory poems. Willing to trace the origins of these two genres, we notice that starting from the very first ages odes and hymns more than once interwine and appear themselves variuosly in non-Christian and Christian literature. However in poetics of the Renaissance, the Baroque and the late Baroque hymns and odes are fixed as different genres, which originated in the Antiquity. In the Middle Ages both of them underwent transformations which step by step led them to becoming genres like we identify them today. In the literature of the Grand Duchy of Lithuania in the 16th–17th centuries it is possible to detect these changes common to all European literature.Despite the fact that Homeric Hymns (still poetic) are quite closely linked with certain ancient rituals, we have no reliable proofs to confirm what like these rituals were in reality. After two centuries Pindar created epinicians (hymn like triumphal odes) which helped to form a way of parting hymns and odes: hymns are to praise god(s), odes – to laud humans. In Hellenistic hymns appealing to gods for creative inspiration, became probably more decorative feature, than having a religious impulse. More precisely, for Hellenistic poets it became a way to imitate an epic and show their literary sophistication.The extant ancient Greek an Roman hymns originated from prayings to gods. For this reason there are common elements in the ancient prayers and hymns. There are several possible views concerned with prayers and hymns, however generally prayers and hymns consist of appealing to god and particular request. Only in hymns willing to praise a god overshadowed the part of request. Moreover, gradually loosing any connection with real rituals, ancient Greek and Roman hymns finally lost it at all. The ancient Roman hymns and hymn like prayers (Carmina Saliaria, Carmen Arvale) are attributed to pre-literary texts. It is believed that they were based and composed on spoken language and only later to them were adapted metric that was borrowed from the Greeks. The authors of the first Christian hymns, recognised Roman culture and had Classical education. They took from pagan sources that, what was in harmony with truths of Christianity. All early Christian hymns are transfused with sincere credit in God. Majority of Christian hymn writers were inspired by classical poetry. They chose different topics from Scripture (concerning lifes of Jesus and Blessed Virgin Mary) and also from lifes of saints and martyrs, because only these themes gained popularity. When the Middle Ages ended, the creation of new Christian Latin hymns almost stopped. In order to uniform an ecclesiastical rituals in churches, all Latin liturgical hymns were revised and some of them newly recomposed, because they were not considered to be a part of Scripture. This survey is important for further researches of literary hymns and odes which were composed in an integral part of Europe – Grand Duchy of Lithuania.
Keywords: hymn; ode; ancient Greek hymn; Roman hymns; literary hymn; liturgical hymns Grand Duchy of Lithuania